Cardiovascular effects of an intravenous bolus of morphine in the ventilated preterm infant. Issue 2 (1st September 2000) - Rutter, N; Evans, N
Abstract : AIM: To examine the cardiovascular effects of an intravenous bolus of morphine, 100 μg/kg, in 17 ventilated preterm infants. METHODS: Heart rate and blood pressure were monitored. Right ventricular output, superior vena caval flow, and the width of the ductus arteriosus were measured by Doppler echocardiography 10 and 60 minutes after the morphine injection, and the values compared with baseline values by the paired t test. RESULTS: There was a small but significant fall in heart rate (2.1% at 10 minutes, 4.3% at 60 minutes) consistent with a sedative effect. There was no effect on systolic, diastolic, or mean blood pressure. There was no significant effect on systemic blood flow as measured by either right ventricular output or superior vena caval flow. Ductal width was significantly reduced by a mean of 16% at 60 minutes, suggesting that normal duct closure was not inhibited. CONCLUSION: No cardiovascular effects of an intravenous bolus of morphine could be detected.